The Influence of Different Cooking Techniques on the Biochemical, Microbiological, and Sensorial Profile of Fish-Based Catering Products - Măzărel, Adrian; Rădoi-Encea, Raluca-Ștefania; Pădureanu, Vasile; Maier, Alina; Matei, Florentina (MDPI AG, 2025)
The present study aims to characterize five fish-based catering dishes, cooked by sous vide, by convection and microwaves in terms of their biochemical content, microbial load, and sensory analysis. The product cooked by using convection had the highest levels of MUFAs, PUFAs, and SFAs and the lowest levels of vitamin PP, riboflavin, and niacin. The sous vide maintained the highest levels of retinol, tocopherol, riboflavin, and niacin. Microwaves triggered the greatest decrease in vitamin content. All microbiological indicators exhibited levels below the acceptable limits, except for the level of fungi in the sous vide cooked product. Shelf life was estimated at 5 days for the product cooked by convection and immediately refrigerated and at 50 days for the product cooked by convection and immediately frozen. The most appreciated product from the sensory standpoint, which falls under fine dining, was the one cooked by convection and served immediately. The sous vide dish, the microwaved dish, and those refrigerated/frozen after cooking were undervalued.
Keywords: catering dishes; cook–chill; cook–freeze; cook–serve; sous vide